Mobile services industry in Singapore : a new entrant's perspective. - Chan, Yun Ying. (2008)
As Singapore continues to liberalize its info-communication industry, new entrants such as StarHub has to position its business units strategically to compete in the dynamic environment. In identifying the changes in perception and behavior, the Mobile Service Providers are not only able to understand their products but their customers better too.